2020
DOI: 10.14336/ad.2019.0810
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Induced Brain-Derived Neurotrophic Factor in Adipocyte Progenitors Contributes to Adipose Tissue Dysfunction

Abstract: Aging-related adipose tissue dysfunction contributes to the progression of chronic metabolic diseases. We investigated the role of age-dependent expression of a neurotrophin, brain-derived neurotrophic factor (BDNF) in adipose tissue. Pro-BDNF expression was elevated in epididymal white adipose tissue (eWAT) with advanced age, which was associated with the reduction in sympathetic innervation. Interestingly, BDNF expression was enriched in PDGFR + adipocyte progenitors isolated from eWAT, with age-dependent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Interestingly, serum BDNF levels didn't differ across severity groups in patients >60yrs, while a reduction of BDNF in patients <60 yrs was observed with the progression of COVID-19 severity. This data reinforces the idea that increased mature BDNF isoform is related to the improvement of metabolic function, while the pro-BDNF isoform is related to the adipose tissue disfunction as observed by Song et al (42). In addition, higher cortisol levels found in obese subjects and a tendency (p = 0.06) for higher levels of the same hormone in patients who died (ICU-death) suggest central hyperstimulation on the hypothalamus-adrenal-pituitary axis during SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, serum BDNF levels didn't differ across severity groups in patients >60yrs, while a reduction of BDNF in patients <60 yrs was observed with the progression of COVID-19 severity. This data reinforces the idea that increased mature BDNF isoform is related to the improvement of metabolic function, while the pro-BDNF isoform is related to the adipose tissue disfunction as observed by Song et al (42). In addition, higher cortisol levels found in obese subjects and a tendency (p = 0.06) for higher levels of the same hormone in patients who died (ICU-death) suggest central hyperstimulation on the hypothalamus-adrenal-pituitary axis during SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 91%
“…Different studies have shown either that circulating BDNF levels are higher in obese subjects than in controls (39,40) or that there are no differences between the two groups (41). An upregulation of pro-BDNF expression in PDGFRα + adipocyte progenitors was indicated as a feature of adipose tissue aging, suggesting that inhibition of BDNF expression in adipocyte progenitors could be potentially beneficial to prevent age-related adipose tissue dysfunction (42). However, in our study, we evaluated serum mature BDNF levels that have opposite effects of pro-BDNF (43).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decreased NAA could be a potential biomarker of central neuronal dysfunction and may be useful in evaluating progression of neuropathy in DM [ 17 ]. Moreover, studies focusing on brain derived neurotrophic factor (BDNF), one of the most essential neurotrophic factors in the brain [ 27 ], and dipeptidyl peptidase-4 (DPP4), initially identified as a therapeutic target for type 2 diabetes [ 28 ], have demonstrated that both BDNF and DPP4 function as an antigenic enzyme involved in hyperglycemia, oxidative stress and inflammation-associated insulin resistance [ 29 ]). These studies provide evidence for the role of increased DPP4 and decreased BDNF in type 2-DM-related cognitive dysfunction [ 30 ], suggesting that DPP4 to BDNF ratio could be a novel biomarker for DM-related cognitive impairment [ 31 ].…”
Section: Potential Mechanism In the Development Of Diabetic Cognitmentioning
confidence: 99%
“…Recently, it was proposed that the BDNF production in progenitor cells of WAT is detrimental to the tissue’s metabolic health during aging. Using the inducible adipocyte progenitor-specific Bdnf knockout (BDNF Pdgfra KO) mice, Song et al demonstrated that abolishing the production of BDNF in adipocyte progenitor cells prevents the aging-induced inflammation and glucose intolerance [ 41 ]. Because in vitro assays showed that pro-BDNF promoted adipocyte apoptosis and reduced the cellular mitochondria content, the authors concluded that an excessive pro-BDNF production in the adipose progenitor cells of aged animals triggered the death of adipocytes, causing the infiltration of immune cells and deterioration of the metabolic fitness.…”
Section: Bdnf In Adipose Tissuementioning
confidence: 99%